2012
DOI: 10.1590/s0100-85872012000200004
|View full text |Cite
|
Sign up to set email alerts
|

La "cultura de la vida": desplazamientos estratégicos del activismo católico conservador frente a los derechos sexuales y reproductivos

Abstract: Desprivatización y postsecular son dos conceptos que circulan con creciente intensidad para explicitar giros importantes en los debates académicos sobre religión y política. Cada uno, a su manera, busca capturar una nueva temporalidad que requiere un replanteo de las principales construcciones analíticas y normativas desde las cuales se dio sentido al fenómeno religioso y a su conexión con la política. El concepto de desprivatización fue propuesto por José Casanova (1994) hace prácticamente dos décadas para no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
35

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 5 publications
0
15
0
35
Order By: Relevance
“…Oponiéndose a la llamada "mentalidad anticonceptiva" (Vaggione, 2012) y en la "defensa de la vida", la IC se posiciona antagónicamente frente a los grupos feministas y por la diversidad sexual (Vaggione, 2014).…”
Section: La Política Sexual De La Iglesia Católica Sobre El Abortounclassified
See 1 more Smart Citation
“…Oponiéndose a la llamada "mentalidad anticonceptiva" (Vaggione, 2012) y en la "defensa de la vida", la IC se posiciona antagónicamente frente a los grupos feministas y por la diversidad sexual (Vaggione, 2014).…”
Section: La Política Sexual De La Iglesia Católica Sobre El Abortounclassified
“…Particularmente en la encíclica Evangelium Vitae (1995), la Iglesia Católica se posiciona como aquella que defiende la "cultura de la vida" frente a la "cultura de la muerte" (Vaggione, 2012). Poder resignificar y tensionar esta posición no es tarea sencilla a nivel subjetivo, ya que implica también superar aquellas concepciones (médicas, religiosas, sociales) que ubican a las mujeres como meras "portadoras", y valorarse como sujetos.…”
Section: Construcción O Deconstrucción Del Embrión Como Personaunclassified
“…They are working in ‡ For example, Prada 18 contexts where access to safe abortion services is legally restricted and where stigma, obstetric violence, and so-called "pro-life" pressure groups are also active. 24,25,35 These hotlines are the result of initiatives carried out by women's collectives and are not a part of any health institution. On the contrary, they are independent spaces that provide health information and that challenge the conventional biomedical/clinical structures, and their services are not offered by doctors or men.…”
Section: Five Safe Abortion Information Hotlines In Latin Americamentioning
confidence: 99%
“…However, anti-abortion groups often target Safe Abortion Information Hotlines in their protest actions. 35 False calls, unnecessarily occupying the telephone line, and reports to authorities are some of the actions that have been taken against these groups, although with little impact.…”
Section: What Information Do the Safe Abortion Information Hotlines Pmentioning
confidence: 99%
“…Four ethical principles form the base of these rights: bodily integrity, personal autonomy, equality, and diversity. particularly in Latin America as well as in its Catholic root nations in (Vaggione 2012;Ruibal, 2014;Zuringa, 2014). Minkenberg (2002) analyzed the relationship between religion and public policies in a comparative study that looks at Western liberal democracies and found a positive correlation between legislatures that restrict abortion and confessional Catholic heritage, particularly in countries where high levels of religiosity still persist.…”
mentioning
confidence: 99%